DNA AND SYSTEMIC DAMAGE INDUCED BY LANDFILL LEACHATES, AND HEALTH IMPACTS OF HUMAN EXPOSURE TO LANDFILLS IN LAGOS AND IBADAN, NIGERIA (2013)
Municipal solid waste landfills in Nigeria are unsanitary. The release of hazardous chemicals via leachates from these landfills may have grievous consequences on the environment and biota. However, there is limited information on leachate induced DNA and systemic damage in vertebrates from different ecological habitats, and human health associated with living around landfills. This study was undertaken to evaluate the cytogenetic and systemic toxicity of leachates and human health impacts of exposure to landfills in Lagos and Ibadan, Nigeria. Olusosun and Aba-Eku landfills in Lagos and Ibadan respectively were purposively selected. Clarias gariepinus (mud catfish), Coturnix japonica (Japanese quail) and Mus musculus (mouse) were exposed to leachates from Olusosun (OSL) and Aba-Eku (AEL) landfills at different concentrations (0 - 50%) for genotoxicity evaluation using the micronucleus assay. Blood collected from Wistar rats (Rattus novergicus) exposed to the leachates was analysed for biochemical parameters (Alanine Aminotransferase, ALT; Aspartate Aminotransferase, AST; and albumin) using standard methods. Liver, kidney and thymus tissues excised from the rats were processed for histopathology. Biochemical Oxygen Demand (BOD), copper, manganese, lead, chromium and cadmium concentrations in the leachates were determined by APHA methods. The health status of residents within 2 and 6 km radius of the landfills was assessed using pre-tested and structured questionnaire. Data were analysed using descriptive statistics, ANOVA and Chi square at p = 0.05. There was concentration dependent, significant induction of micronucleus in the erythrocytes of C. gariepinus (OSL = 1.4±0.0 – 9.6±0.2; AEL = 0.8±0.4 – 8.6±0.6), bone marrow cells of C. japonica (OSL = 1.0±0.2 – 2.1±0.6; AEL = 0.7±0.1 – 3.2±0.6) and M. musculus (OSL = 5.5±0.6 – 18.5±0.0; AEL = 6.5±0.3 – 18.1±1.3). There was significant increase in ALT (OSL= 31.1±2.1 – 52.7±1.6 IU/L; AEL = 30.7±1.5 – 49.5±1.3 IU/L) and AST (OSL = 86.9±13.2 – 168.4±1.0 IU/L; AEL = 84.5±1.5 – 161.9±1.2 IU/L), but significant decrease in albumin level (OSL = 2.6±0.2 – 5.11±0.3 g/dL; AEL = 2.7±0.2 – 5.2±1.2 g/dL) in serum of exposed rats compared to the negative control. Necrosis and vacuolation of the hepatocytes; cortical congestion and haemorrhage in the kidney; and infiltration of macrophages, inflammation and apoptotic lymphocytes in the thymus were observed in exposed rats. The frequencies of these anomalies were higher in OSL than AEL exposed animals. The concentrations (mg/L) of BOD (306.0 – 601.0), copper (0.9 – 3.9), manganese (0.6 – 3.9), lead (0.8 – 2.1), chromium (1.4 – 2.4) and cadmium (0.3 – 2.2) were above NESREA wastewater limits. The frequency of complaints of bad odour (OSL, 95.4%; AEL, 90.1%) and dermal contacts with vermin (OSL, 80.8%; AEL, 54.2%); respiratory (OR=9.7, 95% CI=6.6 – 14.6), dermal (OR=7.2, 95% CI=4.8 – 10.8) and gastrointestinal (OR=7.9, 95% CI=6.2 – 12.1) anomalies were significantly higher among residents nearer (2 km) the landfills. Leachates from Olusosun and Aba-Eku landfills were potential sources of genetic and systemic toxins. Human exposure to toxins from the landfills was associated with adverse health effects. There is need for proper solid waste management to enhance environmental and public health safety.